Pharmacology teaching for dental graduate in India: time for reappraisal - MD FAIZ AKRAM; Seema Manak; Deep Inder; Dr. Asad Khan; Dr. Mohd Tariq Salman (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
India with its vast population and rapidly increasing healthcare demand has a unique position. Dental health is integral to a holistic health care need and a robust dental education system is must. Dental education in India is mainly regulated by Dental council of India, which sets broad guidelines. Universities having dental colleges and institutes develop fine details of curriculum development and evaluation. Subject of General and Dental Pharmacology and therapeutics is an important subject taught to undergraduate dental students during second year of a 4 year duration course. A dental graduate is supposed to be well trained with principles of general and systemic pharmacology and rational therapeutics. This has been set as objective by Dental council of India.Sound knowledge of mechanism of drug action, indications, adverse drug reaction, drug interactions and contraindiacation. Evidence based medicine and rational use of drug is core to the Allopathic system.The practical exercises either on human simulation or computer assisted learning are critical for understanding of pharmacology.The subject of Pharmacology for dental graduate has been allotted 70 hours of theory and 20 hours of practical with almost same syllabus as of medical graduates.  This article is an attempt to highlight the areas of concern with respect to deficiency of teaching hours and needed improvement in curriculum to make it competent to achieve its objective.The authors bring it this much needed topic for discussion among academicians and for the attention of regulatory authorities